Influence of Geometrical Design on Defect Formation of Commercial Al-Si-Cu-Mg Alloy Fabricated by High-Pressure Diecasting: Structural Observation and Simulation Validation - Warda Bahanan; Siti Fatimah; Dong-Ju Kim; I Putu Widiantara; Jee-Hyun Kang; Young Gun Ko (Metals)
Near-net-shaped metal products manufactured by high-pressure diecasting (HPD) encountered more or less critical failure during operation, owing to the development of micro-defects and structural inhomogeneity attributed to the complexity of geometrical die design. Because the associated work primarily relies on technical experience, it is necessary to perform the structural analysis of the HPDed component in comparison with simulation-based findings that forecast flow behavior, hence reducing trial and error for optimization. This study validated the fluidity and solidification behaviors of a commercial-grade Al-Si-Cu-Mg alloy (ALDC12) that is widely used in electric vehicle housing parts using the ProCAST tool. Both experimental and simulation results exhibited that defects at the interface of a compact mold filling were barely detected. However, internal micro-pores were seen in the bolt region, resulting in a 17.27% drop in micro-hardness compared to other parts, for which the average values from distinguished observation areas were 111.24 HV, 92.03 HV, and 103.87 HV. The simulation aligns with structural observations on defect formation due to insufficient fluidity in local geometry. However, it may underestimate the cooling rate under isothermal conditions. Thus, the simulation used in this work provides reliable predictions for optimizing HPD processing of the present alloy.